Intra‐individual metameric variation expressed at the enamel‐dentine junction of lower post‐canine dentition of South African fossil hominins and modern humans. Issue 4 (2nd June 2017) - Pan, Lei; Thackeray, John Francis; Dumoncel, Jean; Zanolli, Clément; Oettlé, Anna; de Beer, Frikkie; Hoffman, Jakobus; Duployer, Benjamin; Tenailleau, Christophe; Braga, José
Abstract: Objectives: The aim of this study is to compare the degree and patterning of inter‐ and intra‐individual metameric variation in South African australopiths, early Homo and modern humans. Metameric variation likely reflects developmental and taxonomical issues, and could also be used to infer ecological and functional adaptations. However, its patterning along the early hominin postcanine dentition, particularly among South African fossil hominins, remains unexplored. Materials and Methods: Using microfocus X‐ray computed tomography (µXCT) and geometric morphometric tools, we studied the enamel‐dentine junction (EDJ) morphology and we investigated the intra‐ and inter‐individual EDJ metameric variation among eight australopiths and two early Homo specimens from South Africa, as well as 32 modern humans. Results: Along post‐canine dentition, shape changes between metameres represented by relative positions and height of dentine horns, outlines of the EDJ occlusal table are reported in modern and fossil taxa. Comparisons of EDJ mean shapes and multivariate analyses reveal substantial variation in the direction and magnitude of metameric shape changes among taxa, but some common trends can be found. In modern humans, both the direction and magnitude of metameric shape change show increased variability in M2 ‐M3 compared to M1 ‐M2 . Fossil specimens are clustered together showing similar magnitudes of shape change. Along M2 ‐M3, the lengths of their metameric vectors are not as variable as those of modern humans, but they display considerable variability in the direction of shape change. Conclusion: The distalward increase of metameric variation along the modern human molar row is consistent with the odontogenetic models of molar row structure (inhibitory cascade model). Though much remains to be tested, the variable trends and magnitudes in metamerism in fossil hominins reported here, together with differences in the scale of shape change between modern humans and fossil hominins may provide valuable information regarding functional morphology and developmental processes in fossil species.